Putting the (R) Ural in Preceptorship - Deirdre Jackman; Florence Myrick; Olive Yonge (Nursing Research and Practice)
Rural nursing is recognized as a unique health care domain. Within that context, the preceptorship experience is purported to be an important approach to preparing safe and competent rural practitioners. Preceptorship is the one-to-one pairing of a nursing student with a professional nurse who assumes the mandate of teacher and role model in a designated clinical/contextual setting, in this case the rural setting. A research gap exists in the literature in which rural preceptorship is specifically explored. The purpose of this paper is to review preceptorship in relation to preparing nursing students specifically for the rural setting. Understanding how preceptorship as an educational model can prepare nursing students to transition to rural practice is an important endeavor. An authentic rural preceptorship may serve to influence the recruitment and retention needs for registered nurses in rural areas. A greater understanding of rural preceptorship serves to illustrate the appropriate support, socialization and contextual competence required to prepare nursing students for rural nursing practice. This paper's review may serve to highlight the research that currently exists related to rural preceptorship and where additional research can contribute to further understanding and development for authentic rural nursing preparation.